PERANCANGAN PROTOTIPE KONVERTER DC KE DC PENAIK TEGANGAN DENGAN VARIABEL TEGANGAN PADA SISI OUTPUT - ., Muclas Ade Putra (Jurnal Teknik Elektro Universitas Tanjungpura, 2014)
Abstrak- Today, the development of technology continues to increase, it is seen more and more electronic equipment used in everyday use, one of them in the use of the converter system. 1 phase DC output voltage that depends on the input voltage supplied to the power amplifier so that the output voltage regulation can be a maximum of a way to make a system that can change the input voltage to the DC voltage level remains a DC voltage having a voltage level that can be changed change , in other words the variable voltage or voltage can be adjusted up and down by using pot. To that end, it is necessary to design a circuit called a DC to DC Converter. The magnitude of the output voltage setting is done by components that are controlled by the PWM method ( Pulse Width Modulation ). The use of PWM signal for this circuit is a circuit that works by cutting up( chopped) a fixed DC voltage levels had become high -frequency pulse train box by using a capacitor as a filter to produce a very smooth ripples and using toroidal transformers as voltage penaik . This study aims to design a DC to DC converter as a push-pull power converter with input voltage of 12 volts DC, and the minimum output voltage range of 14 volts and a maximum voltage of 126 volts. Keywords: DC to DC converters, PWM, push-pull